Makna Dan Implementasi Kurikulum Merdeka Belajar dan Relevansinya Bagi Perkembangan Siswa di sekolah Dasar : Telaah Kritis Dalam Tinjauan Pedagogis - Yan Yan Heryanti; Tatang Muhtar; Yusuf Tri Herlambang (Jurnal Elementaria Edukasia, 2023)
This study aims to explore the meaning and implementation of independent learning curriculum changes as well as its relevance to the development of students especially in elementary schools based on critical analysis in pedagogical reviews. The Independent Learning Curriculum is an idea that is implemented in a policy issued by the government by giving freedom to teachers and students in determining learning systems with the aim of developing superior Human Resources (HR) through fun education for students and teachers by prioritizing on aspects of character development in accordance with the cultural values ​​of the Indonesian Nation. The background of this study is to analyze the meaning and implementation of the independent learning curriculum and its relevance to the development of students in elementary schools. The research method used is literature study with stages 1) selecting source material from journals; 2) looking for references in the literature; 3) reading references; 4) write notes; and 5) present the results of the journal review. Based on journal studies, it can be concluded that changes in the independent curriculum are motivated by the low level of student competence, gaps in the quality of learning and the development of the world of education which is increasingly rapid, especially in the field of technology which requires students to adapt quickly, and the independent curriculum is present as a solution to improve learning , in accordance with the meaning of the independent curriculum, namely independent thinking, independent innovation, independent learning and independence for happiness and in its implementation this curriculum is very relevant to the current development of students.